Building a Green Swimming Pool by Using Concrete with Aggregates from Demolition Waste. (2015) - Hol, Gerard H.P.
Abstract: The paper discribes the way it is possible to make concrete in the severe environment of a swimming hall (high content of chlorine) in which all the coarse natural gravel is replaced by coarse granulate produced out of demolition waste. Normally by replacing natural gravel in concrete with a product such as broken material the amount of cement will increase because the used material will need more water per cubic meter of concrete. Because increasing the water content will also higher the cement content in the same environmental class (EN 206 according to the European concrete standard) in this case the use of the rapid chloride migration test gave the results that made it possible to lower the cement content to a maximum of only 120 kg and apply ground granulated blast furnace slag as a binder component. In this way it was possible to lower the environmental impact of the concrete. In the paper will also be explained and calculated the environmental profit of lowering the cement content as the use of a secondary material as coarse aggregate in concrete. The environmental impact from the primary proposed concrete and used concrete will be shown in LCA made for the project of the swimming hall build in Maastricht in the Netherlands.